Transplantation of umbilical cord blood mononuclear cells increases levels of nerve growth factor in the cerebrospinal fluid of patients with autism - Li, Q.; Chen, C.-F.; Wang, D.-Y.; Lü, Y.-T.; Huan, Y.; Liu, M.; Ge, R.-C.; Chen, X.-W.; Qi, H.-S.; An, L.; Hu, X. (Genetics and molecular research, 2015)
We aimed to evaluate the levels of growth factors in the cerebrospinal fluid (CSF) of patients with autism after transplantation of umbilical cord blood mononuclear cells (CBMNCs). Fourteen subjects diagnosed with autism received transplantation of CBMNCs first through intravenous infusion, and three times subsequently through intrathecal injections. A 2-mL sample of CSF was taken before each intrathecal injection. CSF levels of nerve growth factor (NGF), vascular endothelial growth factor (VEGF), and basic fibroblast growth factor (bFGF) were determined by enzyme-linked immunosorbent assay. All data are reported as means ± SD and were analyzed using the SPSS 10.0 software. One-way analysis of variance with post-hoc F-and Q-tests were performed for comparisons. NGF levels in the CSF were significantly increased after transplantation (213.54 ± 56.38 after the third versus 28.32 ± 12.22 ng/L after the first transplantation; P < 0.05), while VEGF and bFGF levels did not change significantly. Therefore, transplantation of CBMNCs could increase NGF levels in the CSF of patients with autism.